Payment scale economies, competition, and pricing - David Humphrey (European Central Bank (ECB), 2009)
Payment scale economies affect banking costs, competition in payment services, and pricing. Our scale measure relates operating cost to physical measures of European banking "output", finding large economies. This differs from relating total cost to the value of balance sheet assets (the conventional approach). Interest expenses are excluded since differences here are primarily due to mix, not scale. Also, since standard indicators of competition can give inconsistent results, a revenue-based frontier measure is developed and applied to European banks, with little difference evident across countries. Existing differences in bank prices (EC report) are associated with small differences in competition.
Keywords: E41; C53; 330; Bank competition; European banks; frontier analysis; Payment scale economies; Bargeldloser Zahlungsverkehr; Bankentgelt; Skalenertrag; Technische Effizienz; EU-Staaten